An epigenome-wide association analysis of cardiac autonomic responses among a population of welders. Issue 2 (1st February 2017) - Zhang, Jinming; Liu, Zhonghua; Umukoro, Peter E.; Cavallari, Jennifer M.; Fang, Shona C.; Weisskopf, Marc G.; Lin, Xihong; Mittleman, Murray A.; Christiani, David C.
ABSTRACT: DNA methylation is one of the potential epigenetic mechanisms associated with various adverse cardiovascular effects; however, its association with cardiac autonomic dysfunction, in particular, is unknown. In the current study, we aimed to identify epigenetic variants associated with alterations in cardiac autonomic responses. Cardiac autonomic responses were measured with two novel markers: acceleration capacity (AC) and deceleration capacity (DC). We examined DNA methylation levels at more than 472, 506 CpG probes through the Illumina Infinium HumanMethylation450 BeadChip assay. We conducted separate linear mixed models to examine associations of DNA methylation levels at each CpG with AC and DC. One CpG (cg26829071) located in the GPR133 gene was negatively associated with DC values after multiple testing corrections through false discovery rate. Our study suggests the potential functional importance of methylation in cardiac autonomic responses. Findings from the current study need to be replicated in future studies in a larger population.